The transformation of positivist knowledge in the master's degree programme in the sociology of physical culture and sport - Mamedov , Azer Agabala ogly; Peredelskiy, A.A.; Kortunov, V.V.; Panyukov, A.I. (Theory and Practice of Physical Culture, 2026)
Objective of the study is to theoretically substantiate the contemporary transformation of positivist knowledge in the master's professional educational programme in the sociology of physical culture and sport. Methods and structure of the study. The organisation and methods of the study are based on a sequential comparative analysis of, on the one hand, the positivist and, on the other hand, the neopositivist and postpositivist versions of the theoretical and methodological basis of the master's professional educational programme in the sociology of physical culture and sport. Results and conclusions. This research paper provides a comparative analysis of the positivist and neopositivist/postpositivist theoretical and methodological foundations of the master's professional educational programme in the sociology of physical culture and sport. It is shown that the transition of applied sociology to a neo-positivist and post-positivist theoretical and methodological version or platform is due to the following objective reasons: – numerous terminological and contextual contradictions due to the extensive conceptual apparatus and abstract philosophical theorising of science; – the development of digital technologies based on high-level data analysis methods; – bringing specialised applied sociological science and the professional educational model into line with the modern demands of society.